If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + log(x + -7) = log(22x) Reorder the terms: 2 + glo(-7 + x) = log(22x) 2 + (-7 * glo + x * glo) = log(22x) 2 + (-7glo + glox) = log(22x) Remove parenthesis around (22x) 2 + -7glo + glox = glo * 22x Reorder the terms for easier multiplication: 2 + -7glo + glox = 22glo * x Multiply glo * x 2 + -7glo + glox = 22glox Solving 2 + -7glo + glox = 22glox Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-22glox' to each side of the equation. 2 + -7glo + glox + -22glox = 22glox + -22glox Combine like terms: glox + -22glox = -21glox 2 + -7glo + -21glox = 22glox + -22glox Combine like terms: 22glox + -22glox = 0 2 + -7glo + -21glox = 0 Add '-2' to each side of the equation. 2 + -7glo + -2 + -21glox = 0 + -2 Reorder the terms: 2 + -2 + -7glo + -21glox = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -7glo + -21glox = 0 + -2 -7glo + -21glox = 0 + -2 Combine like terms: 0 + -2 = -2 -7glo + -21glox = -2 Reorder the terms: 2 + -7glo + -21glox = -2 + 2 Combine like terms: -2 + 2 = 0 2 + -7glo + -21glox = 0 The solution to this equation could not be determined.
| 4sin(t)=-4+cos(t) | | 2+log^6(x-7)=log^6(22x) | | 2(y-3)+2(x+4)=24 | | 4x+(x-2)(x-3)-3=x^2+5 | | 3+4x=30 | | 4-8b=6b-5 | | 3x+2y+4z=0 | | 3x+6xy=153 | | 1/2x-9=3/4x-5 | | 7r=9t+3 | | 7x-7y-5x+9y= | | 116-75=x | | (5x+2)-(3x+4)=0 | | 8y-3+8y-3=2y | | 10.08+9y=6 | | -3x-12=o | | 22.5-2y=-5 | | (ln)(y)=.61 | | -7x-2/8=-9 | | (6x-9)-(3x+8)=4(x-11) | | -15x^2+27= | | (y-8)(y-3)= | | 3x+6x+9= | | 8x+4x+12= | | 15x+3y=-6 | | 6(x+5)=3[2(2x-3)+1]+5 | | 5(3x-4)=2-2x | | C=0.75n+140 | | 42y+28x= | | 9x+y=10solvey | | -4v+35=-8v+7(5-2v) | | 3(u-5)-7u= |